Wastewater Treatment Using Wood Ash and Cement as Chemical Coagulant - Milkessa Ingida; Gurmesa Bedane; Firanbon Adugna; Degefa Nigusu; Mohammed Hussen; Chala Hailu Sime (International Journal of Analytical Chemistry)
Water is essential for daily activities and maintaining human well-being. However, in many less-developed countries, including Ethiopia, the lack of a well-developed wastewater treatment system leads to contaminated surface water. This poses significant risks to human health. To address this problem, wastewater can be treated using locally available materials such as wood ash and cement as chemical coagulants. The objective of this study was to treat wastewater using these materials. The study involved analyzing a 20-liter sample of wastewater from the Awetu River in Jimma City, Ethiopia. The materials used for the treatment included wood ash, cement, and lemon. Various doses of cement and wood ash were prepared and added to the wastewater. The results showed that 5 g was the optimum dosage for effectively treating the wastewater. The treated water at the optimum dosage exhibited significant improvements in turbidity, total dissolved solids, conductivity, and color, meeting drinking water criteria. Overall, the study concludes that locally available materials such as wood ash and cement can be successfully utilized as chemical coagulants for wastewater treatment. This approach offers a viable solution for improving water quality and reducing the risk of waterborne diseases.